Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation Terhadap Peningkatan Hasil Belajar Fisika Siswa - Eni Sumanti Nasution; Muhammad Rifai; Henry Dinus Hutabarat (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study aims, among others: first, to determine the effect of Group Investigation learning media on learning outcomes in the material of Rotational Dynamics in class XI IPA SMA Negeri 6 Padangsidimpuan. This research was conducted at SMA Negeri 6 Padangsidimpuan with a population of all students of class XI IPA SMA Negeri 6 Padangsidimpuan and as samples were taken 33 students of class XI IPA 2 as the experimental class and 27 students of class XI IPA 3 as the control class using a purposive sampling method. sampling). The study used an experimental method (Experimental Method) and the research data were analyzed by statistical methods. The study used a data collection tool, namely the test of physics learning outcomes. The results of the study show that, first, there is an influence of Group Investigation learning media on the learning outcomes of Rotational Dynamics material in class XI of SMA Negeri 6 Padangsidimpuan.